Design of spiral labyrinth microstrip antenna for DVB-T application - Indra Surjati; Syah Alam; Juliarto Karnadi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Digital television broadcasting is technologies that have been developed by any country in the world. The advantages implementations of digital television broadcasting include reception of picture and sound sharper and better. This paper proposes a new design of spiral labyrinth microstrip antenna feed by microstrip line with array two element for Digital Video Broadcasting Technology (DVB-T) application at work frequency of 586 MHz. The design of spiral labyrinth is used to minimize the dimensions of microstrip patch antenna while maintaining the working frequency at 586 MHz and array technique used to improve gain of antenna. The proposed antenna design was originally a rectangular patch that has been modified by the labyrinth spiral method. From the measurement result obtained return loss of -14.15 dB and VSWR of 1.54 at working frequency of 586 MHz. Bandwidth of proposed antenna is 117 MHz (547 MHz–664 MHz) while gain of antenna is 7.78 dBi. Beside that, using of the labyrinth spiral patch successfully reduced the dimensions of the microstrip antenna until 62.2% compared with the conventional rectangular patch of microstrip antenna. This study is usefull for DVB-T application in order to achieve the maximum signal quality and picture.